ZmBARK1 as a low-temperature tolerance gene in maize germination - Qingyu Xu; Yiying Song; Di Bao; Lingzhi Meng; Hong Di; Lin Zhang; Ling Dong; Xing Zeng; Jiayue Zhang; Chunxiang Li; Jiapeng Xing; Naifu Zhang; et al. (Crop Journal)
Maize (Zea mays L.), a globally significant cereal crop, is produced in vast quantities worldwide. However, its growth is severely constrained by low temperatures, particularly during seed germination, which significantly impairs seedling emergence. In this study, genetic diversity across six germination-associated phenotypic traits (RGR, RSL, RTL, RRSA, RRV, and RSVI) of 304 inbred lines was analyzed, to evaluate the capacity of these lines for low-temperature tolerance. Genome-wide association study (GWAS) was carried out by combining six germination-associated phenotypic traits and genotypic data from 30-fold resequencing. The gene ZmBARK1 was identified through integrated GWAS and RNA-seq analyses, and its association with low-temperature tolerance during maize germination was validated by quantitative real-time PCR (qRT-PCR). ZmBARK1, encoding BRASSINOSTEROID INSENSITIVE 1-associated receptor kinase 1, was located on the bin 4.09 region of maize chromosome 4. Amino acid comparison and subcellular localization analyses revealed that ZmBARK1 is highly homologous to AtBAK1 and is localized to the plasma membrane of the cell, which may be involved in regulating brassinosteroid (BR) signaling. In addition, we revealed the role of ZmBARK1 in low-temperature tolerance during maize germination. Compared with wild-type (WT), the ethyl methanesulfonate (EMS) mutant zmbark1 was characterized by substantially enhanced low-temperature tolerance. Overall, these findings provide promising candidate genes, improve low-temperature tolerance in maize, and advance the understanding of regulatory mechanisms underlying maize’s response to low-temperature stress.